2016
DOI: 10.1007/s10072-015-2465-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic dysfunctions in elderly patients with essential tremor: comparison with healthy controls

Abstract: Questionnaire-based analyses show that patients with essential tremor (ET) may have several autonomic dysfunctions, especially in the cardiovascular and genitourinary domains; yet the laboratory correlates of autonomic dysfunction in ET are unknown and have not been studied. Herein, we explored whether sympathetic and parasympathetic functions differed between control subjects and patients with ET. Seventy-five elderly patients with ET were enrolled in this study, along with 25 age-matched controls. Orthostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 22 publications
2
15
2
1
Order By: Relevance
“…One study defining motor subtype showed less HRV impairment in TDPD patients than patients with akinetic-rigid dominant PD. [16] In another study comparing drug-naive ET patients with controls, there were no differences in the HRV frequency domains between the two groups [23]. While this is in line with our own results, the methodology used in that study did not adhere to the recommendations of the task force [24].…”
Section: Discussionsupporting
confidence: 71%
“…One study defining motor subtype showed less HRV impairment in TDPD patients than patients with akinetic-rigid dominant PD. [16] In another study comparing drug-naive ET patients with controls, there were no differences in the HRV frequency domains between the two groups [23]. While this is in line with our own results, the methodology used in that study did not adhere to the recommendations of the task force [24].…”
Section: Discussionsupporting
confidence: 71%
“…Kim et al reported that ET cases displayed more orthostatic symptoms than controls but the frequency of OH in younger ET patients was similar to that of normal controls. 10 Nonetheless, Damian et al found that with the exception of sialorrhea, there were no autonomic symptoms in ET cases. 11 Thus, the issue of autonomic dysfunction in ET cases is still a topic of debate and reports addressing OH in the cases are scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Obesity is known to contribute to the development of cardiomyopathy. 3,[24][25][26][27] Although the underlying mechanism has been studies F I G U R E 7 MD-1 mediated high-fat diet-induced cardiac pathological remodelling via negatively regulating MAPK and NF-κB signalling. (A, C) Western blot analysis for the phosphorylation levels of MEK, ERK, JNK, p38, IκBα and p65, relative to levels of the total one, in MD-1 −/− hearts and wild-type (WT) mice hearts after high-fat diet feed for 20 wk.…”
Section: Discussionmentioning
confidence: 99%